Atypical crusted scabies in a patient with chronic liver disease caused by hepatitis B and D viruses - Mônica Santos; Gustavo Ávila Maquiné; Carolina Talhari; Antonio Pedro Mendes Schettini (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Crusted scabies is a less common variant of scabies that is highly contagious, difficult to treat and involves infestation by Sarcoptes scabiei var. hominis. The classical clinical presentation includes crusted, scaly and generally non-pruritic lesions usually located on the head, neck, palmar, plantar and periungual region. It was first described in Norway in 1848 in patients with leprosy who presented with crusted lesions. In this study, we report the case of a patient with crusted scabies with florid clinical manifestations and chronic liver disease due to hepatitis B and delta virus infection.